Mathematical modelling of T‐cells activation dynamics for CD3 molecules recycling process. (29th August 2016) - Ali, Qasim; Mustafa, Ibrahim H.; Elkamel, Ali; Touboul, Eric; Gruy, Frederic; Lambert, Claude
Abstract : The down‐regulation of CD3 protein present on the surface of a T‐cell triggers the process of activation. A rapid decrease of CD3 from the surface is required to reach the threshold that is necessary for the continuation of the activation process. Using the flow cytometry technique, it is well established that an amount of down‐regulated CD3 proteins recycle and may appear on the surface of T‐cell. This article studies the impact of recycled CD3 protein that is recruited into the immune synapse at different rates. The population density of T‐cells is distributed over surface protein (CD3) concentration under the framework of population balance models by using a coupled system of PDEs. Such problems need non‐conventional population balance modelling so that classical numerical techniques can be applied. A recently developed efficient numerical method is validated against the analytical and numerical solutions.